The complex role of migration in restructuring rural livelihoods : circulation as a resource? Locality of Leonzoane, Mozambique 1900-2010 - (:unkn) unknown (My University, 2013)
In the context of the demo-economic transition in Sub-Saharan Africa, changes in rural household strategies towards more complex livelihoods, together with the recognition of renewed forms of migration, raise issues around the restructuring of rural economies. This thesis questions the renewed role of Mozambican rural households’ mobilities to understand to what extent they represent a key factor with regards the reshaping of livelihoods in the present post-Apartheid and liberalization context.This work sheds light on the conceptual links between institutional approaches in economics and the notion of circulation in geography in order to analyze the role of mobilities in livelihoods’ strategies in the long term. The analytical approach is based on biographical surveys of 97 Mozambican rural households, and includes both quantitative and qualitative methods. The analysis shows the evolution of intense and circular migration of Leonzoane families to South Africa during colonial times towards more complex forms of mobilities, with a higher degree of working flexibility, in more extended geographical areas within and beyond the historical mining sector. These mobilities rely on a diversity of arrangements embedded in networks, showing evidence of a migration contract in the making, based on household strategies’ circular resources. The analysis of these migration forms together with the reshaping of households’ livelihoods illustrates a highly diversified situation in Leonzoane. While some households show a growing complexity of adjustments of their livelihoods, in which the relative share of agricultural activities tends to decrease, others perpetuate very stable non-diversified livelihoods. Being a fundamental livelihood asset, migration can certainly act as a strategic resource for rural households, but can also be a factor of insecurity or dependency.
Keywords: African Research